Dabrafenib in an elderly patient with metastatic melanoma and BRAF V600R mutation: a case report. (December 2016) - Casadevall, David; Vidal, Joana; Gallardo, Fernando; Zuccarino, Flavio; Arumí-Uría, Montserrat; Dalmases, Alba; Bellosillo, Beatriz; Montagut, Clara
Abstract Background Approximately 50 % of malignant melanomas harbor activating point mutations in theBRAF gene. Typically, these mutations result in the substitution of the amino acid valine at codon 600 of the gene, and 90–95 % of mutations are eitherBRAF V600E orBRAF V600K . Specific BRAF inhibitors such as dabrafenib and vemurafenib are the mainstays of treatment in patients with metastaticBRAF -mutant malignant melanomas. The third most commonBRAF mutation is V600R, which also leads to increased BRAF signaling. Although evidence exists about the activity of dabrafenib and vemurafenib in patients with theBRAF V600R mutation, these patients have been systematically excluded from recent trials with targeted therapies. Case presentation Here, we report the positive results in terms of survival and quality of life obtained with dabrafenib in an 80-year-old Caucasian male patient with a Charlson Comorbidity Index of 8 diagnosed with metastatic malignant melanoma harboring theBRAF V600R mutation. Our patient was treated with dabrafenib for 7 months with minimal toxicity. We also report exploratory analyses of circulating tumor DNA during targeted treatment. Interestingly, the mutation was not detected after starting treatment and became detectable before radiological disease progression. Conclusions Our report suggests that (1) a relevant benefit can be obtained with a BRAF inhibitor in real-world patients with a malignant melanoma harboring aBRAF V600R mutation, and that (2) circulating tumor DNA detection might be of help in assessing tumor burden in everyday clinical practice. The results reported here should encourage the inclusion of patients withBRAF V600R -mutated malignant melanomas in future prospective clinical trials with BRAF inhibitors.